Articular mobilization promotes improvement in functional and inflammatory parameters in a gouty arthritis model - Iranilda Moha Hoss; Lilian de Araujo Pradal; Taciane Stein da Silva Leal; Gladson Ricardo Flor Bertolini; Rose Meire Costa; Lucinéia de Fátima Chasko Ribeiro (Einstein (São Paulo), 2023)
ABSTRACT Objective Gouty arthritis is characterized by painful inflammation due to the deposition of monosodium urate crystals in joint tissues. Despite available treatments, many patients experience ineffective management and adverse effects. This study evaluated a manual therapy protocol involving passive joint mobilization at the peak of inflammation in a gouty arthritis model using functional and inflammatory parameters. Methods Twenty male Wistar rats, 12 weeks old, were divided into two groups (n=10 each): Gouty Arthritis and Control Groups, which were further subdivided into treated and untreated groups (n=5 each). The Gouty Arthritis Group received intraarticular knee injection of 50µL of monosodium urate crystals, while the Control Group received 50µL of phosphate buffered saline. The treatment involved a 9-minutes session of grade III joint mobilization (according to Maitland). Nociception, grip strength, and edema were evaluated before induction (EV0), 7 hours after assessment (EV1), immediately after treatment (EV2), and 1 hour after treatment (EV3). The animals were euthanized, and synovial fluid was collected to analyze leukocyte migration. Results The model mimicked the signs of the Gouty Arthritis Group, with a decrease in the threshold of nociception and strength and an increase in edema and leukocyte count. The mobilization protocol significantly increased the nociceptive threshold and grip strength and reduced edema; however, it did not reverse the increase in leukocyte count. Conclusion Our results suggest that mobilization promotes analgesia and may modulate the inflammatory process owing to reduced edema and subtle attenuation of cell migration, which contributes to strength gain.